Molecular Characterization of Extracellular Vesicles From Human B Cell Lymphomas: Methodological Comparison to Vesicles From Patient Serum - Badal; Md Nasir Uddin; Koivula, Tiia; Islam, Md Khirul; Lehtinen, Laura; Kauko, Otto; Leivo, Janne; Heinonen, Ilkka; Hämälistö, Saara (Wiley, 2026)
Human B cell lymphomas represent a clinically heterogeneous disease group with lack of liquid biomarkers for specific subtype classification. Extracellular vesicles (EVs) hold promises as non-invasive biomarkers, yet their subtype-specific characteristics and clinical utility in these diseases remain largely underexplored. In this study, we have investigated the basic molecular and physical features of EVs from diffuse large B cell lymphoma (DLBCL) cells and from lymphoma patients’ serum. Data from e.g., electron microscopy (EM), Western blotting (WB), immunoassay and mass spectrometry (MS) revealed that the two main DLBCL cell subtype EVs differ in protein expression profile and in overall EV size, with the ABC (Activated B Cell) type having smaller EVs than the GCB (Germinal Centre B cell) type. The ABC type EVs were found significantly more enriched with tetraspanins CD81 and CD9. Parallel experimentation on lymphoma serum EVs revealed shared markers with lymphoma cell line EVs, and that B cell specific marker CD19 can be detected among other serum EVs. Also, to successfully detect markers, e.g. Hsp70 or CD44, in serum EVs we demonstrated to require more intense sample preparation in specific assays. While more patient studies are needed in the future, this pilot study paves the way for understanding the molecular differences in the DLBCL subtypes and for detecting them in the lymphoma EVs.